Madrasah Principal Leadership Management in Instilling Religious Moderation Values - Sari, Gina Wara Wulan; Nasrullah, Yufi Mohammad; Usman, Asep Tutun; Nazib, Fiqra Muhamad (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
Religious moderation is essential for promoting harmony among religious communities in Indonesia. Principals play a crucial role in integrating this principle into school environments. This study aims to examine how the principal of MAN 1 Garut applies religious moderation through his leadership. A descriptive qualitative method with an ethnographic approach was used, with data collected through interviews, observations, questionnaires, and documentation. The findings reveal that the principal applies three stages in promoting religious moderation. The first stage is planning, which is carried out collectively with school staff and stakeholders. The second stage is implementation, where the principal employs a transformational leadership style, focusing on inspiration, empowerment, and providing exemplary behavior to the school community. The third stage is supervision, which involves evaluating and monitoring the effectiveness of the religious moderation program. Despite these efforts, the study identifies challenges, particularly from students who exhibit critical thinking regarding differences in religious views. These challenges require the principal to continuously adapt strategies to foster understanding and tolerance. This study contributes valuable insights for fostering inclusive, harmonious, and tolerant education, particularly in the context of Islamic Religious Education.